A study on semantic and pragmatic features of concessive conjunctions “still”, “yet” in English and “vẫn”, “chưa” in Vietnamese / Nguyen Ngoc Thuy; GVHD: - Nguyen, Ngoc Thuy
The thesis focuses on “A study on semantic and pragmatic features of concessive conjunctions “still”, “yet” in English and “vẫn”, “chưa” in Vietnamese” whose purpose is to find out the similarities and differences of the semantic and pragmatic features of concessive conjunctions “still”, “yet” in English and “vẫn”, “chưa” in Vietnamese. The theory of semantics, pragmatics and conjunctions is used as fundemental background for the research. Data taken from novels, stories in English and Vietnamese are classified and analyzed through quantitative and qualitative methods to prove the semantic and pragmatic features. It is presented in form of tables and figures. The contrastive methods was used to find out the similarities and differences of such conjunctions in terms of semantics and pragmatics. On investigating sentences collected from some bilingual stories and questionnaire done by students from Hanoi University of Business and Technology, the thesis also analyzes mistakes made by Vietnamese students. This analysis, to some extent, leads to some possible suggestions for teachers and students with aims at helping them use these concessive conjunctions in English and in Vietnamese in an effective way.